Acute promyelocytic leukemia evolving from paroxysmal nocturnal hemoglobinuria: A rare occurrence - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
A previously healthy 31-year-old female presenting with dyspnea, iron deficiency anemia, pancytopenia, splenomegaly, and abnormal coagulation tests was admitted to the hospital. Hematology consultation additionally revealed that 71% of cells were indicative of acute promyelocytic leukemia (APL) and the patient tested positive for a t(15; 17) translocation, confirming APL. All-trans retinoic acid (ATRA) therapy was initiated immediately, but the patient exhibited severe dyspnea. This subsequently resulted in circulatory and respiratory arrest, followed by death. Just after death, fluorescein-labelled proaerolysin (FLAER) revealed a paroxysmal nocturnal hemoglobinuria (PNH) monocyte clone of 82%, confirming the diagnosis of PNH. Leukemia can be derived from non-PNH clones in PNH patients. Catastrophic thromboembolic events that could not be controlled with aggressive anticoagulation in a profoundly thrombocytopenic patient without overt disseminated intravascular coagulation (DIC) may suggest co-existent PNH.
Keywords: Leukemia; Promyelocytic; Acute; Hemoglobinuria; Paroxysmal